Validity of PBL-Based Interactive Multimedia Teaching Material Development Using Powerpoint in Elementary School - Nive tiken; Desyandri; Maria Montessori; Melva Zainil (Jurnal Penelitian Pendidikan IPA, 2024)
Education in the 21st century in the era of the industrial revolution 4.0, information technology is developing rapidly and significantly which causes the influence of technology. By using technology, the learning mindset can shift from teacher-centered to learner-centered. The purpose of this research is to develop interactive multimedia teaching materials based on the PBL model using Powerpoint and Canva in elementary school. This type of research is R&D development research with the ADDIE development model. Data collection and data analysis methods using observation sheets, interview questionnaires and validation instruments as well as qualitative and quantitative descriptive analysis methods. The results of the validation of teaching materials showed a "very valid" category in all aspects with an overall average of 91.2 The results of FGDs with teachers stated the feasibility of teaching materials, with the category "very valid" in all aspects with an overall average of 96.96. This multimedia meets the characteristics of learning multimedia that is attractive, easy to operate and very feasible to meet the needs of students.